2004
DOI: 10.1016/j.molcel.2004.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The MKK2 Pathway Mediates Cold and Salt Stress Signaling in Arabidopsis

Abstract: The Arabidopsis mitogen-activated protein kinase (MAPK) kinase 2 (MKK2) and the downstream MAPKs MPK4 and MPK6 were isolated by functional complementation of osmosensitive yeast mutants. In Arabidopsis protoplasts, MKK2 was specifically activated by cold and salt stress and by the stress-induced MAPK kinase kinase MEKK1. Yeast two-hybrid, in vitro, and in vivo protein kinase assays revealed that MKK2 directly targets MPK4 and MPK6. Accordingly, plants overexpressing MKK2 exhibited constitutive MPK4 and MPK6 ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
813
4
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 858 publications
(853 citation statements)
references
References 52 publications
32
813
4
4
Order By: Relevance
“…A potential MAP kinase signaling pathway mediating salt stress responses, composed of MEKK1, MKK2 and the interchangeable MPK4/MPK6 genes, was previously identified in Arabidopsis (Teige et al 2004). Transgenic plants overexpressing MKK2 exhibit constitutive upregulation of stress marker genes and show enhanced salt tolerance.…”
Section: Mapks and Osmotic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential MAP kinase signaling pathway mediating salt stress responses, composed of MEKK1, MKK2 and the interchangeable MPK4/MPK6 genes, was previously identified in Arabidopsis (Teige et al 2004). Transgenic plants overexpressing MKK2 exhibit constitutive upregulation of stress marker genes and show enhanced salt tolerance.…”
Section: Mapks and Osmotic Stressmentioning
confidence: 99%
“…The previously mentioned MAPK cascade (composed of MEKK1, MKK2 and MPK4/MPK6), which functions in salt stress signaling in Arabidopsis, is also functional in cold stress pathway (Teige et al 2004). The mkk2 mutant presents a freezing sensitive phenotype with no observable activity neither for MPK4 nor MPK6, suggesting that MKK2 is an upstream activator of MPK4 and MPK6 in cold signaling.…”
Section: Mapks and Temperature Stressesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover MAPK pathways have been reported to be a part of abiotic stress or ABA signal transduction. Besides a role in disease signaling, the MAP kinase kinase, MKK2 was reported to function as a negative regulator of cold and salt stress signal transduction (Teige et al, 2004). In contrast, guard cell preferentially expressed MPK9 and MPK12 act as positive regulators of ABA signaling at downstream of ROS and Ca 2+ signals and upstream of S-type anion channel regulation (Jammes et al, 2009).…”
Section: Calcium Signal Regulation At the Point Of Aba And Disease Simentioning
confidence: 99%
“…Single and double mutants of the pathway are hypersensitive to salt and will die on high salt concentrations. In a previous work, we showed that a number of MAP2K/MAPK modules, including Arabidopsis AtMKK2/AtMPK6, are able to functionally complement the defect of growth of pbs2Δhog1Δ double mutants [ 4 ].…”
Section: Introductionmentioning
confidence: 98%